The New Role of Principals in Improving Teachers’ Personal Mastery at Schools in Indonesia - Settaraming Algi; Mohd Anuar Abdul Rahman; Lokman Mohd Tahir (Intelektual Pustaka Media Utama, 2012)
The aim of the study was to investigate the new role of principals at senior secondary (SMA) State 1 Lamuru in Bone district in improving teachers’personal mastery. The new roles covers aspects such as designer, teachers, and steward. This sample consists of 40 teachers from secondary school in Lamuru. The researcher developed and tested the questionnaire to ensure the validity and reliability by conducting a pilot study. This study uses the Alpha-Cronbach to analyze and find its values for the principals as a designer, (overall 0.743); the teacher (0.751), and steward (0.678). Meanwhile, the Alpha value the personal mastery was at (0.675). The findings revealed that teachers evaluated their principals at the high level for each dimension. Whereas the finding obtained between the new roles of principals and personal mastery of teachers is at the fair level on each dimension. Therefore, the principals were hoped to play a recent responsibility more effective in schools in such a way the teachers’ personal mastery could be more increased.